Alternative Preparation of Improved NiMo-Alumina Deoxygenation Catalysts - Priecel, Peter; Kubička, David; Vázquez-Zavala, Armando; Antonio de los Reyes, José; Pouzar, Miroslav; Čapek, Libor (Frontiers in Chemistry, 2020)
This investigation deals with NiMo-alumina hydrotreating catalysts effective in the deoxygenation of rapeseed oil. The main goal was to compare catalysts structure, their deoxygenation performance and to link these parameters to reveal important structural information regarding the catalysts intended use. Catalysts were prepared from different precursors (nickel acetate tetrahydrate / molybdenyl acetylacetonate in ethanol and water vs. nickel nitrate hexahydrate / ammonium heptamolybdate tetrahydrate in water), which resulted in their contrasting structural arrangement. These changes were characterized by elemental composition determination, UV-Vis diffuse reflectance spectroscopy, temperature programmed reduction by hydrogen, nitrogen physisorption at 77 K, scanning and transmission electron microscopies and deoxygenation of rapeseed oil. The critical aspect of high oxygen elimination was a homogenous dispersion of NiO and MoO3 phases on the support. It subsequently led to the effective transformation of the oxide form of a catalyst to its active sulfide form well-dispersed on the support. On the other hand, the formation of bulk MoO3 resulted in the separate bulk phase and lower extent of sulfidation.